(untitled) (Everest Advances in Science and Technology, 2025)
Accurate yet computationally efficient modeling is essential for the real-time control of Permanent Magnet Synchronous Generator (PMSG)-based wind energy conversion systems (WECS), particularly when targeting low-cost embedded platforms. Complex multi-mass drive-train models, while capable of capturing torsional dynamics, introduce significant computational overhead that can limit their applicability in rapid control prototyping and embedded implementations. This paper presents a complete single-mass PMSG model derived from aerodynamic, mechanical, and electrical subsystems, expressed in the d-q reference frame for efficient control integration. The modeling approach consolidates the turbine and generator inertias into a single equivalent inertia, significantly reducing the system order while preserving the key dynamics necessary for steady-state and slow-transient analysis. The model is implemented in MATLAB/Simulink with fixed-step solver configurations to ensure compatibility with embedded hardware such as DSPs, FPGAs, and microcontrollers. Simulation results under variable wind speed conditions demonstrate the model’s suitability for maximum power point tracking (MPPT) and DC-link voltage regulation. The proposed lightweight approach provides a balance between model fidelity and execution speed, making it ideal for cost-sensitive, real-time wind energy control applications.